ChemInform Abstract: Copper(I)‐Based p‐Type Oxides for Photoelectrochemical and Photovoltaic Solar Energy Conversion. Issue 45 (October 2016) - Sullivan, Ian; Zoellner, Brandon; Maggard, Paul A.
Abstract: Review: 136 refs.